Pelatihan Kepemimpinan dan Manajemen Organisasi untuk Meningkatkan Kapasitas Perempuan pada Organisasi Fatayat NU Sirampog Brebes - Pribadi, Prayoga; Majid, Muhamad Nurkholis; Hardian, Sakhrul Rifan; Setiawan, Ito; Putranto, Banu Dwi (Universitas Pahlawan Tuanku Tambusai, 2026)
Female members of Fatayat NU still lack confidence in making strategic decisions due to a lack of knowledge about the principles of leadership and organizational management. Unmaximized Potential Fatayat NU has great potential to be an agent of change in society, but this potential has not been fully maximized due to limited leadership and management capacity. One effort that can strengthen the Fatayat NU organization is to improve the leadership and management skills of its members. Based on the results of interviews with the Chairperson of Fatayat NU Sirampog, several obstacles encountered in the organization are the core administrators in each branch do not understand effective leadership in building good communication and in making the right decisions, in addition, the lack of managerial knowledge in organizational management to some extent hampers the process of organizational development. The stages of the activity include data collection, activity preparation, training, mentoring and monitoring and evaluation of activities. The results of the activity are increased knowledge about leadership and organizational management among the Fatayat NU Sirampog Brebes administrators.